(3GdTGaj TQM GdebfYs - (3GdebOSj, GHf bOGeI, YHO GdQMef Hf eMeO Hf CMeO, J (B682 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; heG Jhajbj EdG HGddg Ydjg JhcdJ HGH GdeMQeGJ aj GdfcGM hgf VQHGf eMQeGJ Ydi GdCHO hgf CQHYI CbSGe CMOgG GdeMQeGJ HGdfSH hgf SHY PcQgf Gddg SHMGfg hJYGdis
(3BNQgG (B:s
(3eSCdI (B: (3hEf GQJLYgG aj YOJgG hCTgO Ydi QLYJgG hCbGe GdHjfI Ydi Pdc CfgG RhLJg hCf fcGM aGSO dCfg JRhLs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 329s
(3eYLe GdeDdajf (B2 / 108s
(3cTa GdXfhf (B2 / 1809s
(3TPQGJ GdPgH (B5 / 376s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs